EPIDEMIOLOGY OF SPORTS INJURIES AMONG MIDDLE SCHOOL STUDENTS. Issue 4 (1st February 2017) - Caswell, Shane; Prebble, Matthew; Romm, Kaitlyn; Ambegaonkar, Jatin; Caswell, Amanda; Cortes, Nelson
Abstract : Background: Participation in youth sports is increasing. Yet, limited research on the incidence and severity of injuries within middle school sports(MSS) exists. Objective: Describe the epidemiology of injuries in MSS within a large metropolitan school system located in the US. Design: Prospective descriptive epidemiology. Setting: Injury data collected in 9-MSS programs during 2015–2016. Patients (or Participants): Boy(n=1194) and girl(n=1008) athletes(age=11–14 years) participating in 12 school sponsored sports. Interventions (or Assessment of Risk Factors): Each of the 9 schools was assigned an athletic trainer(AT) who attended all practices and games during the fall, winter, and spring sports seasons of 2015–2016. Main Outcome Measurements: ATs collected injury and athlete-exposure(AE) data. Injury frequencies and rates with 95% confidence intervals(95%CI) for practices and games were described by sport for all injuries (no-time-loss and time-loss). Injury proportions were described by body region. Results: 1643 injuries(182.6±64.8 injuries/school) were reported. Highest rates of injury were: Girls' basketball (39.4/1000AE 95% CI: 34.7–44.1), American football (30.7/1000AE 95% CI: 27.3–34.1), wrestling (28.7/1000AE 95% CI: 24.4–32.9), and girls' soccer (26.3/1000AE 95% CI: 22.1–30.6). Lowest rates of injury were: Girls' volleyball (9.1/1000AE 95% CI: 6.7–11.6), boys' baseball (10.2/1000AE 95% CI: 6.8–13.5), cheerleading (10.6/1000AE 95% CI: 8.5–12.8), and boys' soccer (14.7/1000AE 95% CI: 11.8–17.7). Most injuries occurred during practice (n=889, 54%) compared with games (n=390, 24%). The top three injured body regions injured were: lower extremity (n=744, 45%), upper extremity (n=409, 25%), and head (n=297, 18%). The highest rates of concussion were: football (2.9/1000AE 95% CI: 1.9–4.0), girls' soccer (2.2/1000AE 95% CI: 0.9–3.4), and cheerleading (1.1/1000AE 95% CI: 0.4–1.8). Most concussions occurred during practice (47.3%) compared with games (34.5%). Conclusions: Consistent with previous research a greater proportion of MMS injuries occurred during practices than games. However, our finding that girls' basketball had the highest injury rate differs from prior research. Overall, our rates were higher than those previously reported, yet more precise given our sample size and detailed documentation AE. Our findings highlight the need for medical care at MMS practices and games.